Analisis Faktor Yang Mempengaruhi Perilaku Perawat Dalam Melaksanakan Tindakan Pencegahan Flebitis Pada Pasien Yang Dilakukan Pemasangan IV Line Di Ruang Mawar Putih RSD Sidoarjo: Penelitian Cross Sectional - Caturia Sasti Sulistyana (2013)
Phlebitis is a common form of nosocomial infection that occur in patient with IV line associated with poor adherence of nurse when instal IV line. Some of the factors that influence the nurse’s behavior are knowledge, attitudes, and motivations.The unclear factors that affect the implementation of phlebitis precautions by nurse in Mawar Putih Ward RSD Sidoarjo make incidence of phlebitis every year increased. The objectives of this study was to determine the correlation between knowledge, attitudes, motivation with nurse behavior on phlebitis precautions to patients with IV line in Mawar Putih Ward RSD Sidoarjo. This study used an analitical descriptive cross sectional design. The population were all nurses who install and care the IV line patients with total sample 22 respondent. The independent variable in this study were of knowledge, attitudes, and motivations of nurses and dependent variable was nurses behavior on phlebitis precaution. Data was collected through questionnaire and observation, then was analyzed using Spearman Rho with significant level 0.05. The results showed that there was correlation between knowledge with nurse behavior on phlebitis precaution (p=0,002, r=0,632), attitudes with nurse behavior on phlebitis precaution (p=0,002, r=0,635), motivation with nurse behavior on phlebitis precaution (p=0,001, r=0,643). In conclussion, there are correlation significant between knowledge, attitudes, and motivations nurses with nurse behavior on phlebitis precaution to patients with IV line in Mawar Putih Ward RSD Sidoarjo. It is sugested that nurses can have awareness to change the behavior as standard procedure to prevent phlebitis case. Further study need larger populatons and sample.